Human game : the true story of the "Great Escape" murders and the hunt for the Gestapo gunmen - Read, Simon (2013)
Recounts the events depicted in the movie "The Great Escape," during which Allied airmen broke free of the Stalag Luft III POW camp and how a manhunt twenty years later brought to justice many Gestapo killers who worked there.